EXPERIMENTAL ANALYSIS OF A SINGLE-PHASE PASSIVE COOLING SYSTEM - Bastos, João Pedro Tinoco; Couto, Danillo César Soares; Gonçalves, Gabriel Cerqueira; de Lima, Leon Matos Ribeiro; Mangiavacchi, Norberto (Revista Brasileira de Energias Renováveis, 2018)
The Fukushima Daiichi Accident highlighted the need for new sustainable technologies with high reliability for removing thermal load, in the thermal power area, with focus on nuclear power plants. This technology is designed for heat transfer from a hot source to a cold source by natural convection, without the need of active components, such as pumps or ventilators, reducing costs and improving reliability. In order to analyze the system parameters of such passive systems, with focus on its thermo-hydraulic stability, an experimental campaign was performed using a reduced model built at State University of Rio de Janeiro – UERJ – with a Single-phase Passive Cooling System. Thus, the objective of this work is the experimental characterization of such systems for the analysis of the physical phenomena that drives the flow to unstable regimes and also to validate a 1D numerical model developed within this research project to simulate this kind of systems. Keywords: Natural Convection, Thermal Energy, Nuclear systems.